Meta Analysis of the Effect of the Project Based Learning Model on Students' Critical Thinking Ability in Elementary School Science Learning - Rona; Festiyed; Yerimadesi (Yayasan Nurul Yakin Bunga Tanjung, 2025)
In an effort to achieve the development of students' critical thinking skills in elementary school science learning, various innovative learning models can be used, one of which is the Project Based Learning (PjBL) model. The PjBL model is a learning method that can improve critical thinking skills through problem solving. This type of research is a quantitative meta-analysis study. The meta-analysis study aims to determine how big the effect of the PjBL model is on students' critical thinking skills in elementary school science learning? The collection of articles using the publish or perish application with the keywords project based learning model, critical thinking, elementary school science learning as many as 200 articles and 12 theses. Articles that meet the inclusion criteria are analyzed by calculating the effect size of each journal and thesis. The average effect size analysis of 0.59 is in the moderate category. The PjBL model has an effect on elementary school students' critical thinking skills with r RE = 0.59 in the moderate category. This shows that the application of the PjBL model has an effect on students' critical thinking skills in elementary school science learning. PjBL-based science learning allows students to apply and develop theories, skills, and techniques to solve problems. PjBL enriches students' learning experiences and knowledge, providing more meaningful education in innovative learning